(untitled) (Fiep Bulletin - online, 2011)
The object of this study was to determinate the overweight prevalence based in two indicators (BMI and %BF) and calculated the BMI sensibility and specificity related to the %BF calculated by eight polar bioelectric impedance. Therefore, we evaluated 333 subjects participating in a congress of health care in the city of Maringa-PR. The measurement of weight and height were used to calculate BMI and% BF was obtained by eight polar BIA. Data analysis involved descriptive and inferential statistics. prevalence of obesity observed was 14.4% by BMI, while the percentage of fat showed 29.13% of high level of adiposity. These findings that is necessary certain caution in the epidemiological dates interpretation related to the obesity prevalence, once that it was found low sensitivity and high specificity of BMI. The results indicate that it seems appropriate to adopt the method of eight polar impedance in population studies.